The resilient Middle Triassic habitable climate following Early Triassic severe carbon isotope oscillations: contributions from microbialites, Upper Yangtze Block - Xianfeng Wang; Karem Azmy; Anqing Chen; Shi Sun; Suxiao Li (Frontiers in Marine Science, 2025)
The Permian-Triassic mass extinction was one of the worst crises for life on earth, killing >90% of marine species, which induced the carbon cycle perturbation during the entire Early Triassic. Previous studies indicated the global CO 2 concentration dropped sharply from 2,800 ppmv to a level of approximately 450 ppmv (comparable to the present) at the Early–Middle Triassic boundary. This optimal CO 2 level, a stabilized record of 2‰ δ 13 C carb , persisted throughout the Middle Triassic. While how this long-term habitable CO 2 level was maintained remains puzzling. Here, we examined the sedimentary succession that spans the duration from Late Olenekian (late Early Triassic) to Anisian (Middle Triassic), Upper Yangtze Block. The results show that the volume content of microbialites in the carbonate succession increased significantly after the transition from lower thin-bedded dolostones to upper thick-bedded microbialites, indicating the carbon pump shifted from a low-rate chemical carbonate production system to a high-rate microbial carbonate factory. The expansion of microbial mats responded to enhanced terrigenous input and elevated primary productivity. Coincidentally, the δ 13 C carb curve records a change from strong oscillations to a long-term stability. This turnover coincided with the occurrence of plant fossil assemblages (e.g., from northern Italy) and marine fossil assemblages (e.g., from South China). The findings indicate that the enhanced microbial pump, as a dynamic mechanism for atmospheric CO₂ sequestration, was a key modulator of the Middle Triassic global climate system and helped sustain more resilient ecosystems.